The Exploration of Islamic Education Strategies in the Digital Era in Increasing Students Classroom Active Participation - Kunto Suratno; Abdullah (Bulletin of Pedagogical Research, 2022)
The rapidly evolving digital era, the landscape of education has undergone significant transformation, presenting both challenges and opportunities for Islamic education. This study explores strategic approaches within Islamic educational frameworks to enhance students' active participation in the classroom through digital integration. Utilizing a qualitative method, data were collected through interviews, classroom observations, and document analysis from various Islamic educational institutions. The findings reveal that effective strategies include the integration of digital tools aligned with Islamic values, the use of interactive learning platforms, incorporation of multimedia resources for religious content, and teacher training in digital pedagogies. Moreover, fostering a student-centered learning environment rooted in Islamic principles of discipline, responsibility, and cooperation significantly improves engagement and participation. The research concludes that the thoughtful application of digital strategies in Islamic education not only enhances active classroom participation but also reinforces students' spiritual and moral development. This study offers valuable insights for educators and policymakers in developing effective, value-based digital learning environments in Islamic contexts